Gesture for Linguists: A Handy Primer. Issue 11 (November 2015) - Abner, Natasha; Cooperrider, Kensy; Goldin‐Meadow, Susan
Abstract: Humans communicate using language, but they also communicate using gesture – spontaneous movements of the hands and body that universally accompany speech. Gestures can be distinguished from other movements, segmented, and assigned meaning based on their forms and functions. Moreover, gestures systematically integrate with language at all levels of linguistic structure, as evidenced in both production and perception. Viewed typologically, gesture is universal, but nevertheless exhibits constrained variation across language communities (as does language itself). Finally, gesture has rich cognitive dimensions in addition to its communicative dimensions. In overviewing these and other topics, we show that the study of language is incomplete without the study of its communicative partner, gesture.